Sejarah Awal Masuknya Islam di Selayar (Sebuah Catatan) - Yunus, Abd. Rahim (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
Studies on the entry history of Islam in a place, it is very interesting because of various dimensions with different points of view, of course, based on the theory that strengthen it. From a different perspective is what makes us have a wealth of references. This paper, tries to make a note of the various theories about the arrival of Islam in Selayar. From the existing literature, spawned a variety of analyzes of the historical fact that, based on the approach Navigation and Geography, Selayar be at the shipping trade. that Islam has been present in Makassar since 1550 (but officially the king of Gowa embraced Islam in 1605). Pelras indicate that Selayar possibility has also been accepted Islam before the year 1605, as well as Buton and Gorontalo. This indication is supported by the Selayar not invited by the king of Gowa to Islam. Perhaps at that time, had accepted Islam before Selayar Gowa formally accepted Islam. Calculation of 1605 as the initial entry of Islam in Selayar, in the religious sense is adopted by the king and kingdom. Determination of 1605, based on the arrival of Dato 'Ri Bandang for the second time. If coming for the first time Muslims into the calculation, the initial entry of Islam as the religion of the king and the kingdom is in 1575. data indicate that early Islamic history entry in a screen in the sense, the Muslims have been in Selayar, or there has been no Muslim immigrants living Selayar was before 1575.